2018
DOI: 10.1103/physreve.98.062316
|View full text |Cite
|
Sign up to set email alerts
|

Topologically robust zero-sum games and Pfaffian orientation: How network topology determines the long-time dynamics of the antisymmetric Lotka-Volterra equation

Abstract: To explore how the topology of interaction networks determines the robustness of dynamical systems, we study the antisymmetric Lotka-Volterra equation (ALVE). The ALVE is the replicator equation of zero-sum games in evolutionary game theory, in which the strengths of pairwise interactions between strategies are defined by an antisymmetric matrix such that typically some strategies go extinct over time. Here we show that there also exist topologically robust zero-sum games, such as the rock-paper-scissors game,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 101 publications
(317 reference statements)
0
11
0
Order By: Relevance
“…Knebel and co-authors [12,8] use the topology of the graph describing the interactions in each game to examine the "interplay between the network structure and the strengths of interaction links on global stability" and to classify coexistence networks, that is, those where all actions coexist for all strengths of the interactions. Again, a 3-action cycle seems to persist corresponding to the RSP cycle within the RSPLS game.…”
Section: Introductionmentioning
confidence: 99%
“…Knebel and co-authors [12,8] use the topology of the graph describing the interactions in each game to examine the "interplay between the network structure and the strengths of interaction links on global stability" and to classify coexistence networks, that is, those where all actions coexist for all strengths of the interactions. Again, a 3-action cycle seems to persist corresponding to the RSP cycle within the RSPLS game.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary stages that created Game theory are the ideas about the existence of mixed-strategy equilibria in two-person zero-sum games, followed by the rise of modern mathematical concepts (Geiger, Knebel, & Frey, 2018). In addition, the discovery of the law of development of organic nature by Darwin led to the biological application of the game theory.…”
Section: Game Theorymentioning
confidence: 99%
“…Considerable work has been done studying the meanfield limit model [1,26,12,14,7] and stochastic extensions [5,19]. In the mean-field limit model it has been shown that a constant of motion exists and is a conserved quantity similar to energy or momentum in classical mechanics (though that analogy is not an exact interpretation) [1].…”
Section: Introductionmentioning
confidence: 99%